Innovation in the Family Business Succeeding Through Generations - Schmieder, Joe.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
Schmieder shares a broad range of tools and pathways that family businesses across sectors use to stimulate, execute, measure, and reward innovation. The 50-plus family stories cited in this book will inspire any family enterprise to create a strategy and environment that can stimulate success for many generations to come.
Keywords: Management; Industrial management; Small business; Leadership; Family-owned business enterprises; Management; Innovation/Technology Management; Small Business; Business Strategy/Leadership.; Family Business